Fighting for Their Future: An Exploratory Study of Online Community Building in the Youth Climate Change Movement - Wielk, Emily; Standlee, Alecea (Qualitative Sociology Review, 2021)
While offline iterations of the climate activism movement have spanned decades, today online involvement of youth through social media platforms has transformed the landscape of this social movement. Our research considers how youth climate activists utilize social media platforms to create and direct social movement communities towards greater collective action. Our project analyzes narrative framing and linguistic conventions to better understand how youth climate activists utilized Twitter to build community and mobilize followers around their movement. Our project identifies three emergent strategies, used by youth climate activists, that appear effective in engaging activist communities on Twitter. These strategies demonstrate the power of digital culture, and youth culture, in creating a collective identity within a diverse generation. This fusion of digital and physical resistance is an essential component of the youth climate activist strategy and may play a role in the future of emerging social movements.